Fabrications of the Committee of Five and the Real Facts - Héderváry, Claire de (1957)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Translation of text by an army officer published in newspaper, 19 September 1957.